Application of research protocols in commercial renewable energy research and development in South Africa. - Pahalad, Nivesh (My University, 2014)
ABSTRACT This report addresses the infant commercial renewable energy sector in South Africa (SA). Renewable energy is seen as the alternative to fossil fuel based energy but the consideration of research protocols encompassing more than just technical and statutory requirements needs to be assessed so as to ascertain possible adverse unintended consequences especially when rapidly deploying new technologies. Data was collected via semi-structured interviews with subject matter experts (SMEs). A cross sectional design was thus adopted as a content analysis relating to a single point in time was carried out. The limited number of SMEs and infant nature of this sector in SA lent further credence to this approach and deterred one from a quantitative, longitudinal, case study or comparative approach. The three key findings obtained based on the proposed research questions were: (i) The vast majority of the industry is unaware of the models, though they are in fact familiar with aspects highlighted in the Five Capitals Model on a high level but less conversant with the details of the Twelve Features of Sustainable Societies Model, (ii) The greatest emphasis from industry role players is focussed on the financial aspect of the model with a fundamentally different definition of financial capital(the model defines financial capital as an aggregate of all other capitals whereas industry views financial capital from a purely capitalistic perspective), and (iii) Individual accountability for unaddressed consequences (negligence) was deemed appropriate with collective accountability (upper management) for unintended consequences deemed appropriate. Renewables technology has the potential to propel society to a new age, the transition to this age can however only be quantified over a generation and requires a paradigm shift in order to be realised. Whilst this transition occurs, the possibility for adverse unintended consequences is greatest and needs to be minimised. The adoption and application of the proposed research protocols will undoubtedly assist in achieving this.
MBA 2014
Keywords: Renewable energy sources,Energy policy,Sustainable development.